Let "another number" be x. The "one number" (represented with y) is 12 more than half of x. So that means the other number y = (x/2)+12. The two numbers' total is 60 so y+x=60. Since y is also equal to (x/2)+12, you can substitute y with that, giving you (x/2)+12+x=60.

(x/2)+x=48

1.5x=48

x=32

Now that we know that x is 32, we put it in 32 wherever we see an x in either equation. The easiest one to put in is the y+x=60 equation. So that would give us y+32=60 which means y=28.

Answer: The two numbers are 32 and 28.

(x/2)+x=48

1.5x=48

x=32

Now that we know that x is 32, we put it in 32 wherever we see an x in either equation. The easiest one to put in is the y+x=60 equation. So that would give us y+32=60 which means y=28.

Answer: The two numbers are 32 and 28.